Are Diamond Surface Coatings Immune to Dry Running? - D. Seymour, Michael (Journal of Coating Science and Technology, 2016)
It is well understood that mechanical seal performance is dependent upon the tribology of the seal face materials. Published material is available claiming the advantages of Polycrystalline Diamond (PCD) and its suitability for extended running under dry conditions; indeed, one such claim suggests that PCD coated faces are immune to dry running. In order to investigate this claim, the author undertook a series of rigorously controlled tests to evaluate the performance of mechanical seal faces coated with a Polycrystalline Diamond coating (PCD) against others with Diamond - Like Carbon (DLC) coatings. Seal surface topography was accurately measured before and after testing and was used to evaluate the wear behaviour. From the test results obtained it is concluded that neither coatings are suitable for extended dry running use. However, it was evident that seal faces coated with a new form of DLC identified as, Plasma Assisted - Chemical Vapour Deposition (PA-CVD) performed 18 times longer than the PCD coated ones before reaching a predetermined friction induced temperature. Publications can be cited as evidence that PCD coated seal faces are capable of producing very high frictional temperatures that could, in a dry running situation, allow certain liquid fuels such as flashing hydrocarbons to reach their auto-ignition temperatures. In addition, it was revealed that the PCD coated seal units are being sold at a higher cost than the equivalent DLC coated ones by a factor of three.